Obstacles in the Educational Institution and Ways to Address Them - Hussein, Dr. Zahraa Ahmed Hussein; Sajt, Dr. Jalila Faiadh Sajt (Sulaimani Journal for Humanities, 2026)
Since the mid-eighties of the last century, society has been suffering from many obstacles and difficulties that hinder the work of governmental and local institutions in various fields, and which limit its development, progress and advancement, due to the policy adopted by the ruling regimes, and the great interest in the security and military institution at the expense of other institutions and facilities, which are the basic element for the progress and development of countries, most notably the educational institution, which is the basic element in the progress and development of countries, in addition to the great effects left by the economic blockade, which removed what remained of the infrastructure of the institution, leaving behind administrative corruption and moral deterioration, high rates of unemployment, poverty, drug addiction, and the prevalence of terrorism and crime, which was reflected in all different areas of life.
Keywords: Obstacles; institutions; educational; ways; treatment